Financial Literacy and Consumer Behavior among University Students in the Digital Era - Yuliah Yuliah; Leni Triana; Ina Khodijah (Jurnal Sosial Sains dan Komunikasi, 2026)
The rapid development of digital technology has transformed students’ consumption patterns trought the widespread use of online marketplaces, social media, digital wallets, and cashless payment systems. While these innovations provide convenience in financial transactions, they also increase the risk of impulsive and consumptive spending among university students. This research aims to analyze the influence of financial literacy on students’ consumptive behavior in the digital era. A qualitative descriptive approach was employed involving 20 studentd from the Faculty of Economics and Management, Bina Bangsa University, who were selected trough purposive sampling. Data were collected ini September 2026 through interviews, observations, and documentation, and analyzed using the interactive model of Miles, Huberman, and Saldana. The finding reveal thet students generally possess a basic understanding of financial literacy, particularly in budgeting and saving. However, the implementation of financial knowledge in everyday financial decision-making remains inconsistent. Social media exposure, digital promotions, online marketplaces, and the convenience of digital payment systems encourage impulsive purchasing behavior and weaken financial self-control. The study concludes that financial literacy should be strengthened not only through the enhancement of financial knowledge but also through the development of practical financial skills, self-control, and responsible financial behavior to enable students to adapt effectively to the challenges of the digital era.